PENGARUH MOTIVASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI UNIVERSITAS KANJURUHAN MALANG - Idi Amin Najamudin; Hadi Sunaryo; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to examine and analyze the effect of work motivation, work discipline and work environment on employee performance at Malang Kanjuruhan University both partially and simultaneously. “The population and sample are all employees totaling 58 people. Collecting data through questionnaires. Data analisis in this study using SPSS 16.0. The sampling technique using the Likert Scale method and the data testing techniques used in this study include validity, reliability, multiple linear regression and classical assumptions and testing the research hypothesis”.“The results of the analysis show that partially work motivation and work discipline do not affect employee performance. While the work environment has a significant effect on employee performance. Simultaneously shows that work motivation, work discipline and environment have a significant effect on employee performance”. Keywords: Work Motivation, Work Discipline, Work Environment, and Employee Performance.